Statistics of Industrial Protectionism. Part III. Technological Innovations – A Common European Interest - Krekhivskyi, O. V. (Statistics of Ukraine, 2025)
This article concludes the author's research on the state's influence on industry through targeted political instruments and institutional frameworks. The first two parts of the study demonstrated the effects of industrial protectionism employed by governments to overcome the consequences of wars, epidemics, and crises. The article analyzes transformational changes in European industrial policy in response to the challenges of global instability in particular the financial crisis of 2008–2009 the COVID-19 pandemic and the full-scale Russian aggression in Ukraine. It reveals the restoration of the strategic role of industry as the foundation of economic stability and technological sovereignty. It establishes the strengthening of state intervention in the EU’s industrial development in response to new challenges and threats.The central focus of the study is the state aid instrument for the implementation of Important Projects of Common European Interest (IPCEIs) viewed as a response to market imperfections external trade dependence and internal market fragmentation. Such projects in the EU (in microelectronics hydrogen batteries and digital infrastructure) are characterized by a high level of interstate coordination cover the entire value chain and stimulate private investment. They contribute to achieving economic security breakthrough innovations and ecological transformation.The substantive evolution of this instrument – from a legal exemption to a full-fledged component of industrial policy – demonstrates a rethinking of the role of the state in the innovation-driven development of industry. The updated 2021 rules for state aid expanded priority areas clarified the requirements for first industrial deployment and defined innovation criteria creating the conditions for effective integration of R&D results into the real sector of EU member states.It is emphasized that under conditions of geoeconomics competition critical technologies become instruments of pressure or “weapons” used by unfriendly countries which requires a coordinated proactive policy at the EU level.Ukraine is recommended to take the EU’s experience into account: to create a legal framework to support strategic innovation projects; to align state aid instruments with industrial policy; to define priority technologies; and to participate in EU transnational consortia. Only the synergy of national interests with common European interests will allow the formation of a competitive and resilient industry and accelerate the post-war recovery of the economy.